Studies on the Value of Measurements of Selected Motoric Properties - Osiński, Wiesław (Anthropological Review, 1985)
The author evaluated the reliability of tests characterizing speed, reactivity, strength, dexterity, balance, flexibility and endurance. Coefficients of reliability proved rather high in some tests and unsatisfactory in others. No correlation was found between the age of subjects and the reliability level of the measurements.